Determinants of the use of Liquified Petroleum Gas for South African households - Muanda, Bernard (University of the Witwatersrand, Johannesburg, 2023)
Introduction – South Africa is experiencing the worst energy crisis in decades, and this is causing untold pains for many users across South Africa. At the same time, alternative energy such as liquefied petroleum gas (LPG) usage is lower than similar emerging economies. The purpose of this research is to examine empirically the determinants of LPG usage for South African households. Design methodology – The author uses applies 118 responses to a survey to determine the drivers of LPG usage for South Africa households. To meet these objectives, the author combines the theory of planned behaviour model and partial least square structural equation modelling (PLS-SEM) to validate the hypothesis. Findings – The study found that behavioural control and intention to use LPG are the precursors to the eventual use of LPG. The relationship between behavioural control and LPG usage is stronger than the relationship between intention and the LPG usage. Attitude towards LPG, the perceived behavioural control and the norms, respectively in order of strength, have a positive relationship with the intention to use LPG. Finally,less educated respondents were likely to switch to LPG usage as opposed to the more educated counterparts. Research implications – The study contributes mainly to enhancing government policy with regards concerning the increase of LPG usage by providing key factors to target for marketing and education for the end user. Key policies will contribute to increasing LPG usage, hence positive contribution to the economy. The value of this study is the first to analyse the determinants of LPG usage for South African households using the theory of planned behaviour and structural equation modelling. Hence, it contributes to the debate surrounding the adoption and increase of LPG usage
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: South Africa; Energy; Liquefied Petroleum Gas; Partial Least Squares; Structural equation modelling; Theory of planned behaviour; UCTD; SDG-7: Affordable and clean energy